Comparison of the effect of the mat and reformer pilates exercises on the waist-hips ratio and body compositions of the middle-aged sedentary women - Bastık, Canan; Cicioglu, Halil Ibrahim (Mattioli 1885, 2020)
Study Objectives: The aim of this study was to compare the effects of the 8-week mat and reformer pilates exercises on body composition and waist-hip ratios of middle-aged sedentary women. Methods: Fiftyeight volunteer women participated in the study. Body compositions of women were measured by bioelectrical impedance analyzer, and waist and hip circumference were measured a using tape measure. In the analysis of the obtained data, two-way repeated-measures ANOVA was used. In addition, Bonferroni post-hoc test was used to determine the source of the difference between the groups. In addition, the changes in waist-hip ratios and body compositions of adult women for eight-week exercises were determined using the formula %. = [(Post-test - Pre-test) / Pre-test * 100]. Results: Body mass index, body fat mass, fat-free mass, and waist-hip ratios of the exercise groups were found to be statistically different from the control group (p <0.01). According to these results, the highest body mass index (-1.87%) and body fat mass reduction (-5.35%) were found in the reformer exercise group. In contrast, the highest waist-hip ratio reduction (-1.20%) was in the mat exercise group. Moreover, the highest fat-free mass increase (0.39%) was found to be in the mat exercise group. Conclusion: As a result, 8-week mat and reformer pilates exercises were found to have positive effects on waist-hip ratios and body compositions of middle-age sedentary women.
Keywords: Mat pilates; Reformer pilates; Body composition; Waist-hip ratio